Implementasi Pembelajaran Al-Qur’an Dengan Metode Iqro’ di SMP Negeri 1 Colomadu - Raden Rizki Gilangswara; Zaki Afifi (Kamaya: Jurnal Ilmu Agama, 2026)
The ability to recite the Al-Qur'an according to the rules of tajwid is a fundamental skill for secondary school students. However, at SMP Negeri 1 Colomadu, several students have yet to reach this standard due to limited practice time. The Iqro’ method serves as a practical and progressive learning solution to bridge this competency gap. This study aims to analyze the implementation of the Iqro’ method in depth and evaluate its effectiveness and constraints in improving students' Al-Qur'an recitation skills at SMP Negeri 1 Colomadu. Using a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews with Islamic Education (PAI) teachers, and document analysis. The findings indicate that the Iqro’ method is implemented through three systematic stages: (1) initial competency mapping to determine student placement levels, (2) the application of Active Student Learning Strategies (CBSA) through sima’i (listening) and private tutoring activities, and (3) continuous recording of learning progress in monitoring books. A unique feature of this study is the integration of a specific PAI lesson hour allocated for individual guidance within the dense public school curriculum. The results show that the Iqro’ method effectively improves students' recitation fluency due to its interactive and personalized nature. Nevertheless, its effectiveness is hindered by an unbalanced teacher-student ratio, brief instructional duration, and low intensity of recitation practice at home. Synergy between the school and parents through the use of progress monitoring books remains the key to optimizing learning outcomes.